2017
DOI: 10.3892/ol.2017.5663
|View full text |Cite
|
Sign up to set email alerts
|

PT93, a novel caffeic acid amide derivative, suppresses glioblastoma cells migration, proliferation and MMP-2/−9 expression

Abstract: Abstract. Glioblastoma multiforme (GBM) is the most malignant type of primary brain tumor in adults and can diffusely infiltrate adjacent normal tissue. GBM is therefore rarely cured by surgery or radiation therapy. Matrix metalloproteinases (MMPs) are involved in tissue remodeling and numerous other physiological progresses. The MMPs MMP-2 and MMP-9 are associated with the invasion ability of GBM. PT93 is a novel caffeic acid amide derivative that was first synthesized in 2013. In the present study, the human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Moreover, MMP‐9 and MMP‐2 are two overexpressed MMPs measured in gliomas and the loss of activity of MMP‐9 induced by MMP‐9 hemopexin‐like domain (PEX) exerts inhibitory effects on glioblastoma angiogenesis and intracranial growth of xenograft in nude mice (Ezhilarasan et al, ). The invasive capacity of glioblastoma cells is suggested to be linked to MMP‐9 and MMP‐2, and PT93 could suppress the migration of glioblastoma cells through inhibiting the activities of MMP‐9 and MMP‐2 (K. Li et al, ). miR‐21, a critical miRNA which is highly expressed in glioblastoma cells and links to glioblastoma angiogenesis (Hermansen, Nielsen, Aaberg‐Jessen, & Kristensen, ), was previously suggested to promote angiogenesis in HUVECs via regulation of MMP‐9 and MMP‐2 expressions (Hu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MMP‐9 and MMP‐2 are two overexpressed MMPs measured in gliomas and the loss of activity of MMP‐9 induced by MMP‐9 hemopexin‐like domain (PEX) exerts inhibitory effects on glioblastoma angiogenesis and intracranial growth of xenograft in nude mice (Ezhilarasan et al, ). The invasive capacity of glioblastoma cells is suggested to be linked to MMP‐9 and MMP‐2, and PT93 could suppress the migration of glioblastoma cells through inhibiting the activities of MMP‐9 and MMP‐2 (K. Li et al, ). miR‐21, a critical miRNA which is highly expressed in glioblastoma cells and links to glioblastoma angiogenesis (Hermansen, Nielsen, Aaberg‐Jessen, & Kristensen, ), was previously suggested to promote angiogenesis in HUVECs via regulation of MMP‐9 and MMP‐2 expressions (Hu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al revealed that tetrandrine, which is isolated from the root of Stephania tetrandra S. Moore, inhibits GBM8401 cancer cell migration and invasion in vitro [59]. A novel caffeic acid amide derivative, PT93, suppresses MMP-2 and MMP-9 expression in human GBM cell lines [55]. Our results reveal that TCE inhibits the migration abilities of GBM cells by suppressing MMP-2 expression.…”
Section: Discussionmentioning
confidence: 51%
“…It has also been shown to play a key role in the invasion and metastasis of different types of human cancer cells [50][51][52][53][54]. A few studies have found high expression of MMP-2 has in high-grade astrocytic tumors in comparison to normal brain tissue [55,56]. In addition, the expression levels of MMP-2 were significantly elevated in TMZ-resistant GBM cells in comparison to parental GBM cells [57].…”
Section: Discussionmentioning
confidence: 99%
“…Another caffeic acid ester, CADPE, was studied by Han et al, who demonstrated that it is able to reduce the invasive capacity of human gastric carcinoma and breast carcinoma cells by inhibiting the PMA-dependent MMP-9 activation pathway [205]. A similar inhibition of MMP-2 and MMP-9 activities was found upon treatment with a caffeic acid derivative, PT93 (>30 µM), on immortalized rat HSC-T6 cells [240]. Liu et al instead focused their studies on another compound belonging to the class of phenolic acids (GA) and demonstrated that GA treatment inhibited MMPs' activity in prostate carcinoma cells (PC-3) by increasing the synthesis of the inhibitor TIMP-1 [207].…”
Section: Effects Of Polyphenols On Mmpsmentioning
confidence: 88%